Odpowiedzi

Najlepsza Odpowiedź!
2009-09-16T21:06:30+02:00
4x²+1/(x+1)(x-3) + 1-5x/x-3= 4x²++1/(x+1)(x-3) +(1-5x)(x+1) /(x+1)(x-3) =
4x²+1+x+1-5x²-5x/(x+1)(x-3)= -x²-4x+2/(x+1)(x-3)
1 5 1
  • Użytkownik Zadane
2009-09-16T21:10:58+02:00
4x2+1 1-5x
-------------+---------=
(x+1)(x-3) x-3

4x2+1 1-5x(x+1)
-------------+---------------=
(x+1)(x-3) (x-3)(x+1)

4x2+1 1-5x2-5x
-------------+----------------=
(x+1)(x-3) (x-3)(x+1)

4x2+1+1-5x2-5x
------------------=
(x+1)(x-3)

-x2+2-5x
------------------=
(x+1)(x-3)

-x2-5x+2
------------------
(x+1)(x-3)